(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2022)
Background: A referral system allows patients to have optimal care. This study aimed to provide the current referral pattern in the context of a tertiary care hospital in the periphery of Bangladesh. Materials and methods: This retrospective observational study was conducted from January to December 2020 at the Psychiatry Department of Chittagong Medical College Hospital using data from the referral book. 428 cases were analyzed using SPSS-26, and shown in frequency distribution. Results: Majority responders were male (53%) and from the 21 to 30 age group (31%). Patients referred to Psychiatry Department were more (66.7%) than referred from. Among 27 departments, internal medicine was the highest in referral in both instances (31.1% and 9.6%), followed by neurology (5.8% and 5.1%). The majority of patients (29.4%) had Schizophrenia Spectrum and Other Psychotic Disorder, followed by Bipolar and Related Disorder (25.4 %). Frequently, the name of psychiatric diagnosis was mentioned wrongly by other departments. In majority of cases, other disciplines did not mention a clinical diagnosis in the referral note. Conclusions: Proper awareness regarding referral pattern may aware physicians about the importance of referral to psychiatry, resulting in better patient care. JCMCTA 2022 ; 33 (1) : 103-111